The Utility of ChatGPT in Educational Research—Potential Opportunities and Pitfalls - Turgut Karakose (Educational Process: International Journal)
Background/purpose –Leveraging the latest developments in natural language processing, recent versions of ChatGPT has demonstrated astounding performance on a wide array of tasks through its ability to understand and generate human language, and respond to diverse conversational prompts. Its remarkable performance in numerous applications has also attracted researchers’ attention, prompting investigations into the potential utility of this AI-tool to enhance scientific work. The current paper aims to present a succinct overview of the opportunities and challenges of using ChatGPT in educational research based on the anticipations and analysis of scholars from different fields of research.